Mutation analysis in 54 propionic acidemia patients - Kraus, Jan P.; Lindner, Martin (Journal of inherited metabolic disease, 2012)
Deficiency of propionyl CoA carboxylase (PCC), a dodecamer of alpha and beta subunits, causes inherited propionic acidemia. We have studied, at the molecular level, PCC in 54 patients from 48 families comprised of 96 independent alleles. These patients of various ethnic backgrounds came from research centers and hospitals in Germany, Austria and Switzerland. The thorough clinical characterization of these patients was described in the accompanying paper (Grünert et al. 2012). In all 54 patients, many of whom originated from consanguineous families, the entire PCCB gene was examined by genomic DNA sequencing and in 39 individuals the PCCA gene was also studied. In three patients we found mutations in both PCC genes. In addition, in many patients RT-PCR analysis of lymphoblast RNA, lymphoblast enzyme assays, and expression of new mutations in E.coli were carried out. Eight new and eight previously detected mutations were identified in the PCCA gene while 15 new and 13 previously detected mutations were found in the PCCB gene. One missense mutation, p.V288I in the PCCB gene, when expressed in E.coli, yielded 134% of control activity and was consequently classified as a polymorphism in the coding region. Numerous new intronic polymorphisms in both PCC genes were identified. This study adds a considerable amount of new molecular data to the studies of this disease.
Published online: 27 October 2011
Gesehen am 13.11.2018